Aspek Perbuatan Melawan Hukum Dalam Pengerjaan Proyek Pekerjaan Peningkatan Jalan yang Menimbulkan Kerugian Negara Dalam Perkara Tindak Pidana Korupsi (Studi Putusan PN Medan Nomor 38/PID.SUS-TPK/2022/PN MDN) - Perdana Sani, Tantra; Syahrin, Alvi; Mulyadi, Mahmud (Universitas Ekasakti, 2024)
The Indonesian government itself, in terms of eradicating corruption, has made improvements to the law regarding the eradication of corruption and the establishment of a Corruption Eradication Commission institution to support law enforcement. The government has established Law Number 31 of 1999 concerning the Eradication of Corruption Crimes as amended by Law Number 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning Eradication of Corruption Crimes. Therefore, it is important to examine unlawful acts in Corruption Crimes. This research is aimed at analyzing unlawful acts in Corruption Crimes which cause state losses in corruption cases, how to analyze the evidence of corruption crimes in the Medan District Court Decision Number 38/Pid.Sus-TPK/2022/PN Mdn, as well as analysis in Work on Road Improvement Work Projects Which Cause State Losses in Corruption Crime Cases in Medan District Court Decision Number 38/Pid.Sus-TPK/2022/PN Mdn. The research method used is normative juridical research, which is supported by primary and secondary data sources. All legal materials were collected using library research techniques using document study data collection tools. Analyzed qualitatively. In eradicating criminal acts of corruption, especially in the application of unlawful elements, we must be able to prove whether there has been an unlawful act in which there has been a violation of statutory regulations or failure to implement statutory regulations which then has the potential to cause financial losses to the State. In this research the defendant violated the provisions of Government Regulation Number 58 of 2005 concerning Regional Financial Management, Presidential Regulation Number 54 of 2010 concerning Procurement of Government Goods/Services and its amendments, and Minister of Home Affairs Regulation Number 13 of 2006 as amended by Minister of Home Affairs Regulation Number 21 of 2011 concerning the Second Amendment to Minister of Home Affairs Regulation Number 13 of 2016 concerning Guidelines for Regional Financial Management. With state losses worth Rp. 1,173,762,681.06,-